Optimal placement of distributed generation using colliding bodies optimization - Kalidas Babu, Gera; V. Ramana rao, P (International Journal of Engineering and Technology, 2018)
The present paper foremost objective is to resolve best practicable location of solar photovoltaic distribution generation (DG) of several cases using different distribution load power factors and to analyze power loss reduction. This objective achieved by a recent developed method, the so called colliding bodiesâ€™ optimization algorithm, to perceive optimum location. Performances of colliding bodiesâ€™ optimization algorithm have been evaluated and compared with other search algorithms. The execution to test viability and efficiency, the proposed collid-ing bodiesâ€™ optimization is simulated on standard IEEE 38 bus radial distribution networks. The acquired outcome from colliding bodies Optimization algorithm exhibits the possible location of distributed generation through different pre assumed load power factors compared to the other stochastic search bat and genetic algorithm.Â Â